Cultural resilience: The production of rural community heritage, digital archives and the role of volunteers. (August 2017) - Beel, David E.; Wallace, Claire D.; Webster, Gemma; Nguyen, Hai; Tait, Elizabeth; Macleod, Marsaili; Mellish, Chris
Abstract: The following paper addresses a lacuna in the literature relating to the concept of resilience. To date, cultural activity in relation to resilient communities has been given little attention and this paper will highlight how the lens of community heritage activities and the 'bottom-up' role of volunteer labour can act as a catalyst for building more resilient communities in rural areas. This develops from rural areas that have strong place identities, formed through the reproduction of traditional cultural practices alongside contemporary influences. These identities are performed and constructed through a varied repertoire of knowledges, histories, and customs. Their on-going production can be central to community identity as they attempt to make visible their own accounts of history and place. Beyond this, community heritage organisations have also begun to have grounded 'impacts' that move away from heritage interests alone, often revitalising buildings and providing community services. This will be used to highlight how such cultural heritage activity builds collective resilience. A further trend (in the UK) has been for community heritage groups to digitise collections, due to the perceived transformational effect for community regeneration, the strengthening of community cohesion and the potential socio-economic benefits. In partnership with community heritage groups, the CURIOS (Cu lturalR epositories andI nfo rmationS ystems) project explores two case studies in rural Scotland asking how community activity, connectivity and digital archives can support interest in local heritage as well as help develop more resilient communities.